2011
DOI: 10.1158/1078-0432.ccr-10-1430
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Colon Cancer Response Following Treatment with AZD1152: A Preclinical Analysis of [18F]Fluoro-2-deoxyglucose and 3′-deoxy-3′-[18F]Fluorothymidine Imaging

Abstract: Purpose: To determine whether treatment response to the Aurora B kinase inhibitor, AZD1152, could be monitored early in the course of therapy by noninvasive

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 47 publications
1
34
0
Order By: Relevance
“…The wide range of pretreatment FLT uptake values may be explained by the wide variation in proliferation (13,26,27). Other mechanisms including relative use of salvage versus de novo precursors for DNA synthesis could also influence FLT uptake (28,29). We used the SUV at 60 minutes as a semiquantitative measure of this biochemical activity.…”
Section: Discussionmentioning
confidence: 99%
“…The wide range of pretreatment FLT uptake values may be explained by the wide variation in proliferation (13,26,27). Other mechanisms including relative use of salvage versus de novo precursors for DNA synthesis could also influence FLT uptake (28,29). We used the SUV at 60 minutes as a semiquantitative measure of this biochemical activity.…”
Section: Discussionmentioning
confidence: 99%
“…The ADC dispersion rate averaged in the range 50-250 Hz was shown sensitive to treatment of colorectal tumor SW620 with barasertib (AZD1152) [51], known to induce the formation of new chromosomic structures at subcellular level, increased cell size and eventually apoptosis [52].…”
Section: Adc Dispersion Ratementioning
confidence: 99%
“…Using a cell-based assay, FLT retention in cells was found to be strongly associated with TK1 expression (5). In some cases, tumor cells predominately synthesize the nucleosides that are needed for cell growth de novo (6), which results in low [ 18 F]FLT tracer avidity in the proliferating tumor, leading to false negative results (7,8). Clearly, in order for [ 18 F]FLT-PET imaging to "light up" proliferating cells, a number of factors must come into play.…”
Section: Introductionmentioning
confidence: 99%
“…In this respect, translational imaging research has been considerably emphasized for correlating [ 18 F]FLT-PET imaging readouts with target biomarker changes that are measured by other tools in the preclinical and clinical arenas. A number of preclinical [ 18 F]FLT-PET translational imaging studies have reported using early investigative anticancer agents, including the MAP/ERK kinase inhibitor PD-0325901 (11), the epidermal growth factor receptor (EGFR) inhibitor erlotinib (12), the mTOR inhibitor everolimus (13), the P-cadherin antibody PF-03732010 (14), and the aurora B kinase inhibitor AZD1152 (7). Using the tumor models that are responding to therapy, these reports showed that treatment-induced modulation of the targets is closely associated with a decline in [ 18 F]FLT retention.…”
Section: Introductionmentioning
confidence: 99%